Comparative study of different types of genes with Islamic rhetorical theory in Hafez poetry - Parvin Mashayekh; Seyyed Mahmoud Seyed Sadeghi; Seyed Jafar Hamidi (مطالعات زبانی و بلاغی)
Religious heritage is one of the most important poetry elements of poets in expressing inner feelings and their thoughts so that they have established an intertextual relationship in their poems with the word of revelation. One of the poets whose Qur'anic expressions and meanings are considered one of his most important sources of art is Hafez. In the present paper, based on the descriptive-analytical method, the comparative study of the intertextual aspects of the gene with the Islamic rhetorical theory in the Hafez Divan have been examined. Accordingly, the types of deliberate, implicit, implicit hidden intertexts and their comparative features in Islamic rhetoric, including guaranteeing, referring, solving, eliminating, paraphrasing, referring, adapting, concluding, and examining, are studied in this work. The purpose of this study is to study the use of the previous texts based on the theory of genes and their adaptation to Islamic rhetoric theory. Based on the present study, the most intertextitial, intermediate, and implicit interpolation in the Islamic language is Talmij. Thereafter, the most intentional inhumanity is the most frequent. The creativity of the author attracts and persuades the audience in how to use the earlier texts and the use of the intertextual element, and the creation of an ingenious link between the earlier texts and the present text, artistically.